Finishing materials for facades and interiors of Art Nouveau buildings examples of Ukraine and Poland - Ivashko, Yulia; Korovkina, Ann; Yermolenko, Iryna; Kuśnierz-Krupa, Dominika; Kobylarczyk, Justyna (My University, 2021)
The article is devoted to the study of building materials for Art Nouveau buildings in the cities of Ukraine and Poland and the experience of their restoration using modern materials and technologies. Considering the vastness of Art Nouveau (Secession style) heritage in Ukraine and Poland, the authors limited themselves to only one narrow aspect – finishing materials and four cities – Kyiv, Kharkiv, Cracow and Lodz. The example of Rodzianko's apartment in Kyiv shows what finishing materials were used at the beginning of the 20th century. The buildings of the northern national romanticism, in which natural raw stone was widely used, were distinguished by the specifics of the decoration. The Polish Art Nouveau version formed in the mainstream European trends and under the direct influence of the Vienna Secession. On the example of objects in Сraсow and Lodz, different methods of finishing the facades of buildings with various functional purposes were shown. The scientific novelty of the article is the analysis of the chemical compositions of paints and plasters of the Secession period, and modern methods of restoration of such objects.
Keywords: Art Nouveau; facades and interiors; finishing materials; Kyiv; Kharkiv; Cracow; Lodz; Restoration